The Effect of Forest Management PEC, FSC, ISO 38200:2018 on Wood Industries Competitiveness: Evidence from Indonesia - Purwanto, Agus; Asbari, Masduki; Ong, Freddy; Prameswari, Mirza; Santoso, Priyono Budi; Hutagalung, Leo; Sihite, Otto Berman; Primahendra, Virza (International Journal of Psychosocial Rehabilitation, 2020)
Sustainable business is the dream of every organization and industries. In order to sustain, the organization and industries needs to perform well and able to competition with others. Pioneer industry such as wood are also aims for the same thing. There are three crucial industries that contribute in sustaining the world’s wood industries, and they are Forest Stewardship Council (FSC), Program for the Endorsement of Forest Certification (PEFC) and ISO 38200:2018. The purpose of this research was to determine the effect of Forest Management of FSC Chain of Custody, PEFC Sustainable Forest Management and ISO 38200:2018 Chain of Custody of wood and wood-based products towards the business competitiveness of wood industries in Indonesia. This research was conducted among several wood processing companies or industries that uses wood as main raw material in Indonesia. The respondents are 372 employees of wood industries as top management, manager and staff that have plan or have implement FSC, PEFC and ISO 38200:2018. The background of the research is because of inadequate in research data on PEFC, FSC and ISO 38200:2018 which implemented particularly in wood Industries in Indonesia. The data collection was carried out by using electronic questionnaire which distributed to 372 employees in the wood industries starting August 2019 until November 2019. The collected data was analyzed using Structural Equation Model (SEM) and Linear Structural Model (LISREL) version 8.70. The results of the analysis showed that implementation FSC Chain of Custody, PEFC Sustainable Forest Management and ISO 38200:2018 Chain of Custody of Wood and Wood-based are significantly and positively affect the business competitiveness like increase improvement in the customer satisfaction index, increase sales growth and market share. This research is high in novelty value as it proposes a model for FSC, PEFC, ISO 38200 and business competitiveness of wood industries in Indonesia.This research could be adapted and adopted by other countries or in other regions.Furthermore, this research can open the pathway for the top management of wood industry or other industry alike to increase the business competitiveness and performance.